Pengenalan - Abdul Karim, Khairuddin (Penerbit UTM, 1998)
This book was translated from English to Malay. The attached/given chapter explains the responsibility of an engineer in systematic exploration over a given site. Other chapters covered are minerals and rock, superficial deposition, subsurface water, etc.